The hen who dreamed she could fly : a novel - Hwang, Sŏn-mi, 1963- (Penguin Books, 2013)
"No longer content to lay eggs on command only to have them carted off to the market, a hen glimpses her future every morning through the barn doors, where the other animals roam free, and comes up with a plan to escape into the wild--and to hatch an egg of her own"--